Towards smart dairy nutrition: Improving sustainability and economics of dairy production - Manfred Schönleben; Joachim Mentschel; Luboš Střelec (Czech Journal of Animal Science, 2020)
To satisfy increasing food and nutrient supply requirements for our growing future human population, farmers and staple food producers carry vital responsibilities. Especially farmers with ruminant livestock like dairy cows transform otherwise for human consumption unsuitable fibre into highly nutritious milk and meat. Nevertheless, dairy farmers are challenged increasingly by the consequences of global warming. Economic risks like feed supply and volatile commodity prices need to be balanced, also taking into account the increasing environmental awareness of end-customers. Focusing just on emissions, dairy production is contributing an essential part of the total carbon footprint emitted by the agricultural sector. Since rumen degradability of feed was identified by the Food and Agriculture Organization of the United Nations as one of the most influential parameters in reducing the carbon footprint of dairy farming, the desire to exploit leverage potential for efficiency increases can be considered exceptionally high. Although the positive effects of improved feed, in other words, neutral detergent fibre rumen degradability for